Key Drivers of Purchase Intent by Indian Consumers in Omni-Channel Shopping - Rajan, C. R.; Swaminathan, T. N.; Pavithra, M. R. (Indian Journal of Marketing, 2017)
10 years ago in India, any retail focused on making the products available in the stores and help customers buy the same when they walked in. Today, with the availability of the Internet, smart phones, and tablets, the patterns of customer buying have changed. There are numerous apps and websites available to help customers find the right product, recommendations, offers and discounts at the click of a button anywhere, anytime. The boundaries of retail channels are eroding - a customer could be standing in a retail store and accessing information and offers available on a website. In the current scenario, shoppers are not just shopping online, but are merging their online and offline shopping practices. There are multiple channels available to customers and they, at a time, access one channel while in the middle of another channel, like accessing a mobile app from a store. Brick and mortar (B&M) retailers also face a continuous challenge from e-commerce retailers, who work with lower overhead costs and provide the best deals to customers on every purchase. Considering the paucity of literature and lack of adequate research on omni-channel in the Indian context, and emergence of implementing a true omni - channel strategy as a tool for the full integration of the offline and the online customer shopping experience, this study was undertaken to analyze the factors which influenced the purchase intent of the customer in omni-channel buying. Both qualitative and quantitative research was carried out to arrive at the variables, and hypotheses and statistical packages such as Excel and SPSS were employed to test the hypotheses. From this study, it emerged that in an omni - channel approach to consumer purchase intent by an Indian consumer, for it to be impactful, it must be supported by systems that make the order status visible to customers. There is likely to be a better buyer response if the product codes of the product across channels are the same. Further location-based promotions positively impacted purchase intent. Companies would , therefore, benefit by adopting digital strategies that augment consistent product codes across channels, real time tracking of orders, and location based promotions based upon this research.